(untitled) (LEGAL DIALOGICA, 2025)
This study aims to identify the legal principles underlying the application of legitimate portion rights based on the Civil Code. In addition, this study reviews the factors that cause the non-implementation of legitimate portion rights through legal analysis. This study employs three primary approaches: legislation, conceptual, and case study. Data is analyzed qualitatively to assess the alignment between legal norms and the practical application of the legitimate portion in court rulings. The results of the study show that the legal principles of inheritance based on the Civil Code include: inheritance due to death, saisine for heirs, individual, bilateral, and ranking. Of all these principles, the most relevant to the law of legitimate portion are the principles of inheritance due to death, saisine rights, and ranking. The factors causing the non-implementation of legitimate portion in Indonesia include: legal factors, socio-cultural factors, economic factors, administrative factors, and internal family factors. Therefore, this requires reform through expanded protection, preventive mechanisms, non-litigation channels, notification of heirs, legal harmonization, and strengthened regulations and socialization to ensure effective implementation. This study recommends the need to enhance legal education for the public regarding inheritance rights and simplify legal procedures to make the implementation of the legitimate portion more effective and efficient. Collaboration between the government, law enforcement agencies, and the public is crucial to ensure fair and responsive protection of inheritance rights in line with social and cultural dynamics. Abstrak: Penelitian ini bertujuan untuk mengetahui prinsip-prinsip hukum yang mendasari terhadap penerapan hak legitime portie berdasarkan KUHPerdata. Selain itu, penelitian ini meninjau faktor-faktor yang menyebabkan tidak terlaksananya legitime portie dengan analisis hukum. Penelitian ini menggunakan metode tiga pendekatan utama yaitu Perundang-Undangan, Konseptual, dan Studi Kasus. Data dianalisis secara kualitatif untuk menilai kesesuaian antara norma hukum dan praktik penerapan legitime portie dalam putusan pengadilan. Hasil penelitian menunjukkan bahwa prinsip-prinsip hukum kewarisan berdasarkan burgerlijk wetboek diantaranya; pewarisan karena kematian, hak saisine bagi ahli waris, individual, bilateral, dan penderajatan. Dari keseluruhan prinsip tersebut yang paling relevan dengan dengan hukum hak legitime portie adalah prinsip kewarisan karena kematian, prinsip saisine, dan prinsip penderajatan. Adapun faktor-faktor yang menyebabkan tidak terlaksananya legitime portie di Indonesia, yakni; faktor yuridis, faktor sosial-budaya, faktor ekonomi, faktor administratif, dan faktor internal keluarga. Sehingga hal ini memerlukan adanya reformasi melalui perluasan perlindungan, mekanisme yang preventif, adanya jalur non-litigasi, notifikasi ahli waris, harmonisasi hukum, serta penguatan regulasi dan sosialisasi agar terlaksana secara efektif. Penelitian ini merekomendasikan perlunya meningkatkan edukasi hukum kepada masyarakat terkait hak waris dan penyederhanaan prosedur hukum agar pelaksanaan legitime portie lebih efektif dan efisien. Sinergi antara pemerintah, penegak hukum, dan masyarakat penting untuk memastikan perlindungan hak waris yang adil serta responsif terhadap dinamika sosial budaya.